Impact of participating AIMS Student Mobility Programme: a UiTM perspective - Zainab Mohd Noor; Asmahan Abd. Razak; Judith Gissip; Ing Masria Mustafa (Penerbit Universiti Kebangsaan Malaysia, 2020)
ASEAN International Mobility for Students (AIMS) programme offers an opportunity for students of Higher Education Institutions (HEIs) in Malaysia to study abroad while undertaking degree programmes in a local university. The purpose of this study is to examine the impact of students’ participation in AIMS programme at a prominent higher education institution in Malaysia. The study explores the impact of the programme on participants by highlighting personal and professional development. The participants in this study were 40 respondents who participated in the AIMS programme at the institution. This study adopts a mixed methods research designs which integrates both quantitative and qualitative data to measure participants’experience. Data was collected and analysed from a questionnaire, observations, written report and video-recording to understand students’ learning experiences, cross-cultural skills, communication skills and critical thinking skills. The results show that AIMS programme develop positive social impact on students’ personal cross-cultural learning experiences and real communication skills, developments which are hard to gain in a monogamous campus social context. The study also identifies the real-life skills set they acquired which can be used in their academic and their personal lives. The number of students’ outbound involvement in AIMS at the institution is low, due to limited fields offered in AIMS programme and also limited budget. Therefore, a proper planning and continual revision on the course offered by each member institutions is recommended and an increase in financial support is desirable to support a larger student participation in the programme.